Mediating and Moderating Effects of Psychological Detachment on the Association Between Stressors and Depression: A Longitudinal Study of Japanese Workers. Issue 3 (29th March 2023) - Kiuchi, Keita; Sasaki, Takeshi; Takahashi, Masaya; Kubo, Tomohide; Yoshikawa, Toru; Matsuo, Tomoaki; Liu, Xinxin
Abstract : The clinical significance of this paper is the finding of the coexistence of the mediating and moderating effects of psychological detachment (PD) with respect to the effects of stressors on depression over long intervals. It emphasizes the importance of tailored interventions targeting stressors and PD. Abstract : Objectives: This study examines the mediating and moderating effects of psychological detachment (PD) based on the stressor-detachment model in the long term. Methods: Two waves of Web-based surveys, 28 months apart, yielded 3556 responses from Japanese workers. Comparisons between models that included mediating and moderating effects of PD and reverse direction mediating effects (strain → PD → stressor) were made by structural equation modeling. Differences in depression as a strain between combinations of high and low stressors and PD were also examined. Results: The best-fitting model was the moderation/reciprocal partial-mediation model. The effect of PD was significant in the group with stable or decreasing stressor. Conclusion: According to the worker's level of stressors, PD, and depression, targeted interventions may effectively prevent physical and mental health problems caused by chronic stress.